PENGARUH KOMPETENSI SOSIAL GURU PENDIDIKAN AGAMA ISLAM TERHADAP HASIL BELAJAR SISWA KELAS XI IPS 1 DI SMA NEGERI 1 GUNUNG TOAR KECAMATAN GUNUNG TOAR - Eka Matra; Wigati Iswandhiari; Sopiatun Nahwiyah (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2020)
This study aims to determine the effect of social competence of Islamic Religious Education teachers on learning outcomes of students of class XI IPS 1 in SMA Negeri 1 Gunung Toar and to find out the factors that influence social competence on learning outcomes of students of class XI IPS I in SMA Negeri 1 Gunung Toar Gunung Toar District. Based on observations made at SMA Negeri 1 Gunung Toar showed several symptoms as follows: 1) Lack of communication between teachers and students of class XI IPS 1 at SMA Negeri 1 Gunung Toar. 2) Between teachers and students not getting along effectively in class XI IPS 1 at SMA Negeri 1 Gunung Toar. 3) Lack of mutual respect between teachers and students in class XI IPS 1 in state high schools. 4) Lack of mutual openness and trust between teachers and students of class XI IPS 1 at SMA Negeri 1 Gunung Toar. 5) Students do not pay attention to the teacher explaining and tend to daydream. Data collection techniques used were observation, questionnaires and documentation. In processing data using simple linear regression analysis techniques with the help of SPSS. Based on the percentage achieved in this study it can be seen that the social competence of PAI Class XI IPS 1 teachers in SMA Negeri 1 Gunung Toar, Gunung Toar District contributed significantly. The regression equation is Y = 21,308 + 1,494X. The equation shows that the value of the teacher's social competency coefficient is 1.494, which means that if the teacher's social competency increases by one unit, the learning outcomes will increase by 1.494 units. After knowing the influence between the two variables, then proceed with finding the coefficient of determination, to find out how much the social competence of teachers contributes to learning outcomes. Thus, the magnitude of the effect of the social competence of teachers on learning outcomes of students of class XI IPS 1 in SMA Negeri 1 Gunung Toar, Gunung Toar District is 26.5%, which means it has an influence while 73.5% is influenced by other factors.